Ionospheric-Thermospheric Responses in South America to the August 2018 Geomagnetic Storm Based on Multiple Observations - Shah, Munawar; Abbas, Ayesha; Ehsan, Muhsan; Aiber, Andres Calabia; Adhikari, Binod; Tariq, M. Arslan; Ahmed, Junaid; De Oliveira-Júnior, José Francisco; Yan, Jianguo; Melgarejo-Morales, Angela; Jamjareegulgarn, Punyawi (My University, 2022)
The ionospheric storm time responses during August 2018 are investigated over South American region using multiple observables, for example, Global Navigation Satellite System (GNSS) derived vertical total electron content (VTEC) from International GNSS Service, magnetic field data, geomagnetic indices, global ionospheric maps, thermospheric mass density (TMD), and [O/N2] ratio measurement. Strong-ionospheric and upper-atmospheric disturbances affected the ionospheric variables with long duration during the storm recovery phase and following after. First, daytime VTEC (9:00-20:00 UT) presented variations of >15 TECU during days 25 to 30 of August 2018 in low and middle latitudes of South America, this after sudden storm commencement (SSC). Furthermore, nighttime (21:00-24:00 and 00:00-05:00 UT) VTEC presented low values (5<TECU<7) in mid-latitude region after SSC event during the main phase, followed by high values (>8 TECU) in the recovery phase. Second, the ionospheric values during the storm main phase and following after, at low-and mid-latitudes, caused the equatorial ionization anomaly to expand due to prompt penetration electric field. Furthermore, VTEC enhancements are likely to occur few hours after the SSC of 25 August 2018, while enhancements of TMD and [O/N2] ratio started to appear later on 26 and 27 of August 2018.
Keywords: Geomagnetic storm; Global Navigation Satellite System (GNSS); INTERMAGNET; ionosphere; thermosphere